FROM THE HISTORY OF VETERINARY SERVICE AMONG CENTRAL ASIAN PEOPLES DURING THE FIRST AND SECOND RENAISSANCE PERIODS. - Djamila Badridinovna Sayfudinova (European Journal of Agricultural and Rural Education, 2022)
In Uzbekistan, the veterinary service is critical to the development of animal husbandry. The study of its history, along with educating the staff in the spirit of patriotism, shows that our history is multifaceted, meaningful, and exemplary. In the scientific literature of the first IX-XII and the second XVI-XV centuries, which took place in the lives of the peoples of Central Asia, veterinary data and historical sources require a scientific study of the history of the field